2019
DOI: 10.1093/cz/zoz040
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between personality traits and the physiological stress response in a wild mammal

Abstract: Glucocorticoids (GCs) are involved in the regulation of an animal’s energetic state. Under stressful situations, they are part of the neuroendocrine response to cope with environmental challenges. Animals react to aversive stimuli also through behavioral responses, defined as coping styles. Both in captive and wild populations, individuals differ in their behavior along a proactive–reactive continuum. Proactive animals exhibit a bold, active-explorative and social personality, whereas reactive ones are shy, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 67 publications
4
28
0
Order By: Relevance
“…Personality traits activity and immobility, measured in the OFT, had a moderate repeatability, suggesting they are reliable personality traits for red squirrels, in both alpine and plain sites (Brehm & Mortelliti, 2018; Carter et al., 2013). This is similar to other studies on the same species, where repeatabilities for activity and immobility were also moderate (Mazzamuto et al., 2019; Santicchia, Wauters, Piscitelli, et al., 2020; Wauters et al., 2019), and on other studies on rodents where repeatability of activity measured in the OFT were from moderate to high ( Tamiasciurus hudsonicus : Boon et al., 2008; Tamias striatus : Montiglio et al., 2012; Sciurus carolinensis: Mazzamuto et al., 2019, Santicchia, Wauters, Dantzer, et al., 2020; Marmota flaviventer : Petelle et al., 2019; Peromyscus maniculatus , Myodes gapperi , Blarina brevicauda: Brehm et al., 2019, Brehm et al., 2020).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Personality traits activity and immobility, measured in the OFT, had a moderate repeatability, suggesting they are reliable personality traits for red squirrels, in both alpine and plain sites (Brehm & Mortelliti, 2018; Carter et al., 2013). This is similar to other studies on the same species, where repeatabilities for activity and immobility were also moderate (Mazzamuto et al., 2019; Santicchia, Wauters, Piscitelli, et al., 2020; Wauters et al., 2019), and on other studies on rodents where repeatability of activity measured in the OFT were from moderate to high ( Tamiasciurus hudsonicus : Boon et al., 2008; Tamias striatus : Montiglio et al., 2012; Sciurus carolinensis: Mazzamuto et al., 2019, Santicchia, Wauters, Dantzer, et al., 2020; Marmota flaviventer : Petelle et al., 2019; Peromyscus maniculatus , Myodes gapperi , Blarina brevicauda: Brehm et al., 2019, Brehm et al., 2020).…”
Section: Discussionmentioning
confidence: 85%
“…Recent studies on rodents measured exploration in the OFT using different variables, such as duration or frequency of behaviours observed, and reported repeatabilities from low to moderate ( Marmota flaviventer : Petelle et al., 2019; Myodes glareolus : Schirmer et al., 2019). Previous studies on the same species and on a different squirrel species also found low repeatability values for exploration measured in the OFT ( Sciurus vulgaris : Santicchia, Wauters, Piscitelli, et al., 2020; Wauters et al., 2019; Sciurus carolinensis : Santicchia, Wauters, Dantzer, et al., 2020) and among‐individual variation in the duration of exploration behaviours in the OFT was low, compared to other behavioural measures taken during the same tests (see Table S2; Santicchia, Wauters, Dantzer, et al, 2020; Table 1; Santicchia, Wauters, Piscitelli, et al., 2020; Table 2; Wauters et al., 2019). Hence, behaviours related to pure exploration by this species occur rarely in such tests.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has for several species been shown that conspecific individuals have different personalities [1,2]. These different personalities are expressed by consistent behavioral responses under various conditions, that can vary with different variables e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These different personalities are expressed by consistent behavioral responses under various conditions, that can vary with different variables e.g. population density, stress and enrichment [2,3,4]. The personality of an animal can influence its welfare, as these responses can vary between individuals, i.e.…”
Section: Introductionmentioning
confidence: 99%